Implementation of a Persuasive Approach in Fostering Self-Awareness and Discipline of Male Students - Alvina Alvina; Endang Ekowati; Tamyis Tamyis (Global Education Journal, 2026)
Islamic boarding schools are Islamic educational institutions that play a strategic role in shaping the character, morals, and personality of students as a whole. This study aims to describe the implementation of a persuasive approach in fostering self-awareness and discipline among male students at Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung, analyze the forms of persuasive approaches applied, and identify the supporting and inhibiting factors in the student development process. This study employed a qualitative approach with a field research design. Data collection techniques included observation, in-depth interviews, and documentation. The research subjects consisted of the boarding school caretaker, Islamic teachers, administrators, and male students. Data analysis used the Miles, Huberman, including data condensation, data presentation, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The results showed that the implementation of the persuasive approach was carried out through interpersonal communication, advice, motivation, role modeling, habituation, and emotional approaches that were continuously applied in the students' daily lives. This approach was able to improve students' self-awareness, responsibility, and discipline, making them more aware of carrying out their obligations and obeying boarding school regulations. The conclusion of this study indicates that the persuasive approach is effective in fostering self-awareness and discipline among male students because it is able to create behavioral changes that originate from students' internal awareness in a humane and sustainable manner.